PENGEMBANGAN BAHAN PELATIHAN DESAIN SISTEM PEMBELAJARAN BAGI GURU BAHASA INDONESIA SMA - Budiyono, Herman; Rubiati, Rubiati; Setyonegoro, Agus (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2014)
Purpose of this research is produce "Training Material of Study System Design for Senior High School Indonesia Language Teacher" as according (1) requirement of teacher; (2) condition of expansion; (3) effectif, (4) can increase teacher interest; and (5) earns for teacher training. This research adopts expansion models Dick and Carey (2009). The sequence: determination of general purpose, study analysis, identification of initial ability, writing of purpose of special, assessment expansion of directive reference, strategy expansion, election and matter expansion, scheme and expansion of formative evaluation, revision, and scheme and expansion of evaluation sumatif. Result of this research, in general shows product " Training Material", very good. Suggestion, that product exploited by Senior High School Indonesia Language Teacher and exploited for further education expansion. Keyword: Development, training materials, design, learning systems